Digital portfolio in the development of documentary competence in university students - Cornejo-Sánchez, Jesús Fernando (2020)
Translators face numerous challenges for doing their work, not only linguistic but also multimedia-related challenges. For this reason, translation undergraduate students must develop their documentary competence with a digital portfolio. The aim of this research is to demonstrate the effect of using a digital portfolio for developing documentary competence in the translation students from a private university in Lima. This research is quantitative and has a quasi-experimental design. It has been applied to a course of direct translation for two semesters. The sample was 32 students, 16 of them for control group and 16 for experimental group. A test was given before and after using the digital portfolio, so that documentary competence can be measured in its three dimensions: thematic field, terminology and textual genres. Findings suggest that the digital portfolio is effective for developing documentary competence in the experimental translation group. The use of a virtual platform allows students to develop documentary or instrumental competence and to familiarize themselves with the use of different multimedia resources as repository.